1991
DOI: 10.1007/bf01447244
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a counterflow plasma reactor

Abstract: Modeling of a counterflow plasma reactor is presented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…In the calculation, T 01 = 8,500 K and U 01 = 350 m/s have been chosen as the plasma jet-inlet temperature and velocity, as in [10]. Figures 2,3,4,5,6,7,8,9 present the modeling results for the case with the same plasma jet-inlet temperature and Figure 2 shows that due to the counter injection of the quenching gas, a distinct gasinterface layer with great temperature gradient (called as stagnation layer in Ref. [6]) is formed between the plasma torch exit and the counter-flow injector exit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the calculation, T 01 = 8,500 K and U 01 = 350 m/s have been chosen as the plasma jet-inlet temperature and velocity, as in [10]. Figures 2,3,4,5,6,7,8,9 present the modeling results for the case with the same plasma jet-inlet temperature and Figure 2 shows that due to the counter injection of the quenching gas, a distinct gasinterface layer with great temperature gradient (called as stagnation layer in Ref. [6]) is formed between the plasma torch exit and the counter-flow injector exit.…”
Section: Resultsmentioning
confidence: 99%
“…In early 1990s, a plasma reactor with counter-flow injection was developed in the High Temperature and Plasma Laboratory of the University of Minnesota and successfully employed for synthesizing various advanced ceramic powders including carbides, nitrides, oxides, solid solutions, etc. [3][4][5]. In such a reactor, particulate matter (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4], experimental and modeling studies were conducted concerning the characteristics of the laminar thermal plasma reactor with counter-injected liquid feedstock. Those studies showed that many parameters, such as the operation parameters of the plasma torch (e.g., the input power, the working-gas flow rate, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the traditional plasma reactors with lateral carrier-gas injection, the plasma reactor with counter injection of the cold fluid (gas or liquid) can improve the reaction environment significantly, such as enhancing the residence time of the reactants in the hot core region, stimulating the intimate mixing of reactants with the plasma, and controlling the particle sizes by reducing particle coagulation or coalescence, etc. In early 1990s, a counter-flow liquid injection plasma reactor for synthesis of advanced ceramic powders was developed in the High Temperature and Plasma Laboratory of the University of Minnesota [3,4]. In recent years, the plasma reactor has been employed for synthesizing aluminum nano-particles with counter-injection of pre-heated carrier-gas (argon) and AlCl 3 vapor with temperature in the range of 165-180°C [5].…”
Section: Introductionmentioning
confidence: 99%